Examining the Effectiveness of Spirituality-Based Psychological Counseling on Fear of Failure in Female Junior High School Students - Bahari, Soheila; Hosseininasab , Seyed Davoud; Azmodeh, Masoumeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to determine the effectiveness of spirituality-based psychological counseling on fear of failure in female junior high school students in District 3 of Tabriz. Methods and Materials: The research method was quasi-experimental with a pre-test post-test design, including control and experimental groups and a follow-up period. The statistical population comprised all female junior high school students in District 3 of Tabriz, totaling 8,256 students across 30 schools. The research sample was randomly selected from two schools in this district, and 20 volunteer students from each school were chosen. To measure problem-solving skills, the Heppner and Petersen questionnaire was used, and for the intervention, the spirituality therapy package by Galanter and Siegel was employed. For hypothesis testing, multivariate analysis of variance and Bonferroni’s within-group test were used. Findings: The examination of research hypotheses indicated that spirituality-based psychological counseling is effective and enduring on the components of fear of failure in female junior high school students. Conclusion: Spirituality-based psychological counseling effectively reduces fear of failure in female junior high school students, demonstrating lasting impacts. This intervention can be a valuable addition to educational support programs, promoting psychological resilience and academic success.